2011
DOI: 10.23939/chcht05.04.463
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Regularities of the Processes of Accumulation and Destruction of Microorganisms in Water at Bubbling of the Different Gases

Abstract: Kinetics of microorganisms accumulation (the first stage) and destruction (the second stage) in water dispersion in the air atmosphere and at bubbling of oxygen, argon and helium has been investigated. The accumulation of microorganism takes place in oxygen and in the air atmosphere at the first stage. The microorganisms destruction was observed at bubbling of the system by argon, helium during the whole process, however, in the air atmosphere and oxygen -in the second stage. Mathematical model of these two pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
(5 reference statements)
0
6
0
1
Order By: Relevance
“…We observed that sonication enhanced the breakup of floc caused by microorganisms clumping together, which made them more susceptible to disinfection [11]. A mathematical model for the gas (Ar, He, О 2 ) effect on the process of water purification from Bacillus bacteria type in the absence of cavitation was proposed [13]. Our investigations showed that the efficiency of microorganism destruction under the influence of cavitation was explained by cell membrane destruction induced by cavitation.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…We observed that sonication enhanced the breakup of floc caused by microorganisms clumping together, which made them more susceptible to disinfection [11]. A mathematical model for the gas (Ar, He, О 2 ) effect on the process of water purification from Bacillus bacteria type in the absence of cavitation was proposed [13]. Our investigations showed that the efficiency of microorganism destruction under the influence of cavitation was explained by cell membrane destruction induced by cavitation.…”
Section: Introductionmentioning
confidence: 84%
“…The actions of cavitation alone, of bubbling gas alone and of the simultaneous action of cavitation and gas bubbling upon the disinfection of sewage water, natural water and microbial dispersions were considered in our previous study [10][11][12]. We observed that sonication enhanced the breakup of floc caused by microorganisms clumping together, which made them more susceptible to disinfection [11]. A mathematical model for the gas (Ar, He, О 2 ) effect on the process of water purification from Bacillus bacteria type in the absence of cavitation was proposed [13].…”
Section: Introductionmentioning
confidence: 99%
“…4. The process flow diagram for the porous composites production: HEMA, water and cyclopentane volumetric tanks (1,7,8); initiator, PVP, PEG, mineral filler and AgNO 3 weighing tanks (2, 3, 4, 5, 6); mixers (9-11); mold with the initial mixture (12); mold with porous composite (13) and porous block (14) The proposed technological scheme will allow to produce the composite billets of arbitrary dimensions, which can be given the desired shape and size after mechanical treatment. This is important when using composites as bone implants.…”
Section: Tablementioning
confidence: 99%
“…Ultrasound energy is often used in the chemical industry to improve and intensify the technological processes. Ultrasound is acoustic vibrations with the frequencies of 2 • 10 4 Hz and higher [1,2]. When propagating in any phase, including a liquid one, such vibrations cause a range of specific effects, in particular ultrasonic cavitation and the initiation of chemical reactions [3].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have presented data on the disinfection by cavitation which is generated by ultrasonication, hydrodynamic effects or electro-impulse discharges. Nowadays the most investigated and studied are the processes of water disinfection under ultrasound cavitation [2,8,15,20], but this method is suitable only for the treatment of small water reservoirs, which is explained by the low efficiency and great power consumption of this process. The efficiency of this method is explained by the authors by the microbe cells rupture, which occurs in the area of the pressure gradients effect and the temperature pulsation.…”
Section: Introductionmentioning
confidence: 99%